C-Phycocyanin-derived Phycocyanobilin as a Potential Nutraceutical Approach for Major Neurodegenerative Disorders and COVID-19- induced Damage to the Nervous System - Pentón-Rol, Giselle; Marín-Prida, Javier; McCarty, Mark F. (Current Neuropharmacology, 2021)
The edible cyanobacterium Spirulina platensis and its chief biliprotein C-Phycocyanin have shown protective activity in animal models of diverse human health diseases, often reflecting antioxidant and anti-inflammatory effects. The beneficial effects of C-Phycocyanin seem likely to be primarily attributable to its covalently attached chromophore Phycocyanobilin (PCB). Within cells, biliverdin is generated from free heme and it is subsequently reduced to bilirubin. Although bilirubin can function as an oxidant scavenger, its potent antioxidant activity reflects its ability to inactivate some isoforms of NADPH oxidase. Free bilirubin can also function as an agonist for the aryl hydrocarbon receptor (AhR); this may explain its ability to promote protective Treg activity in cellular and rodent models of inflammatory disease. AhR agonists also promote transcription of the gene coding for Nrf-2, and hence can up-regulate phase 2 induction of antioxidant enzymes, such as HO-1. Hence, it is proposed that C-Phycocyanin/PCB chiefly exert their protective effects via inhibition of NADPH oxidase activity, as well as by AhR agonism that both induces Treg activity and up-regulates phase 2 induction. This simple model may explain their potent antioxidant/antiinflammatory effects. Additionally, PCB might mimic biliverdin in activating anti-inflammatory signaling mediated by biliverdin reductase. This essay reviews recent research in which CPhycocyanin and/or PCB, administered orally, parenterally, or intranasally, have achieved marked protective effects in rodent and cell culture models of Ischemic Stroke and Multiple Sclerosis, and suggests that these agents may likewise be protective for Alzheimer’s disease, Parkinson’s disease, and in COVID-19 and its neurological complications.
Keywords: Phycocyanobilin